ORGANIZATIONAL MAINTENANCE OF DISTANCE LEARNING FOR THE HIGHER PEDAGOGICAL EDUCATION - Fedorova Я.Б.; Osipova, H.B.; Sedov А.О. (Journal of Information Technologies in Education (ITE), 2010)
The article deals with the organizational maintenance of distance learning for higher pedagogical education at two basic levels: national level of the organisation of distance learning system and at level of educational process with use of distance learning technologies.